Validation of attenuation imaging coefficient, shear wave elastography, and dispersion as emerging tools for non-invasive evaluation of liver tissue in children - Cetiner, Metin; Schiepek, Felix; Finkelberg, Ilja; Hirtz, Raphael; Büscher, Anja K. (Frontiers in Pediatrics, 2023)
The number of children with acute and chronic liver disease is rising. Moreover, liver involvement may be limited to subtle changes in organ texture especially in early childhood and some syndromic conditions, such as ciliopathies. Attenuation imaging coefficient (ATI), shear wave elastography (SWE), and dispersion (SWD) are emerging ultrasound technologies providing data about attenuation, elasticity, and viscosity of liver tissue. This additional and qualitative information has been correlated with certain liver pathologies. However, limited data are available for healthy controls and have mainly been raised in adults. This prospective monocentric study was conducted at a university hospital with a specialization in pediatric liver disease and transplantation. Between February and July 2021, 129 children aged 0-17.92 years were recruited. Study participants attended outpatient clinics due to minor illnesses excluding liver or cardiac diseases, acute (febrile) infections or other conditions affecting liver tissue and function. ATI, SWE, and SWD measurements were performed on an Aplio i800 (Canon Medical Systems) with an i8CX1 curved transducer by two different investigators with long-standing experience in pediatric ultrasound according to a standardized protocol. Considering multiple potential covariates, we derived percentile charts for all 3 devices relying on the Lambda-Mu-Sigma (LMS) approach. 112 children were considered for further analysis, excluding those with abnormal liver function and under-/overweight (BMI SDS<-1.96/> 1.96, respectively). Age range was 0-17.92 years (mean 6.89±0.50SD), 58% were male. The mean duration of the ultrasound examination (basic ultrasound plus SWE, SWD, and ATI) was 6.67±0.22 minutes and it was well tolerated in 83% (n=92) of cases. While ATI was related to age, SWD was found to depend on BMI SDS, and SWE on abdominal wall thickness and sex. ATI correlated with neither SWE nor SWD, but SWE was correlated with SWD. Our study provides norm values and reference charts for ATI, SWE, and SWD considering important covariates including age, sex and, BMI. This may help to implement these promising tools into imaging diagnostics of liver disease and to improve the diagnostic relevance of liver ultrasound. In addition, these noninvasive techniques proved to be time-effective and highly reliable, which make them ideal for application in children.